Model Implementation Problem-Based Learning with a Differentiated Learning Approach to Improve Abilities, Computational Thinking Student - Milenia, Krisna; Rahman, Eka Fitrajaya; Nuraeni, Ani (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
Based on the results of the non-cognitive diagnostic assessment conducted by the author in class X PPLG 1 SMK Negeri 11 Bandung, the computational thinking abilities possessed by students still need to improve. In addition, based on the results of observations, teachers have not implemented differentiated learning optimally. This study aims to improve students' computational thinking abilities by applying problem-based and product-differentiated learning models. The research method used is Classroom Action Research (CAR), carried out in 3 cycles. The subjects of this study were 20 students of class X PPLG 1. The results of this study show that applying the PBL model and product-differentiated learning can improve student learning outcomes in the DPLG subject, with the achievement of completeness in cycle I at 45%, cycle II at 70%, and cycle III at 45%. Students' computational thinking abilities also increased from achieving completeness of 10% to 75%. The effectiveness of learning carried out in cycles I and II are included in the reasonably practical category, as evidenced by the N-gain of 60% and cycle III of 41%, which can improve students' computational thinking skills.